Representation Of Violence In The Film Malignant 2021 - Devina Natalie; Cosmas Gatot Haryono (Jurnal Info Sains : Informatika dan Sains, 2024)
Violence refers to physical, verbal, or psychological behaviors carried out to injure or harm others or other beings, including acts of physical abuse, bullying, and warfare. Its impacts often harm societies and individuals, violating human rights principles. Violence can affect the mental and physical conditions of individuals who are victims of it. The purpose of this research is (1) to analyze the meaning conveyed in the film "Malignant" and (2) to analyze the representation of violence depicted by actors within the film "Malignant." The method used by the researcher is a qualitative approach, where the film "Malignant" by James Wan, released in 2021, serves as the primary data source analyzed. The analysis technique used is semiotic analysis from Charles Sanders Peirce, consisting of signs, objects, and the use of signs (interpretant). The analysis results show that the film "Malignant" combines supernatural horror elements with mystery and thriller elements to create a gripping story with many surprises. "Malignant" creates a tense atmosphere with various captivating scenes. It narrates the life of a woman who often receives visions of gruesome murders, which disrupt her peace. These murders are carried out by a terrifying figure. The woman named Madison, portrayed by Annabelle Wallis, also experiences violence from her husband while she is pregnant, leading to a miscarriage. Additionally, at the beginning of the story, her husband is also killed by the same terrifying figure.